Disparities in health care outcomes between immigrants and the majority population in Germany: A trend analysis, 2006-2014. - Patrick Brzoska (PLoS ONE, 2018)
Immigrants often encounter barriers in the health system that may affect their health care outcomes. In order to better cater to the needs of immigrants, many health care institutions have increased their efforts in recent years to provide services which are more sensitive to the needs of an increasingly diverse population. Little is known about whether these efforts are successful. This study examines difference in outcomes of tertiary prevention between immigrants and the autochthonous population in Germany over the period of 2006-2014.The analysis is based on a 10% random sample of routine data on completed tertiary preventive treatments in Germany during 2006-2014. Four different indicators of treatment effectiveness were compared between patients with a nationality from Germany, Portugal/Spain/Italy/Greece, Turkey and Former Yugoslavia using logistic regression adjusted for demographic/socioeconomic factors. Interaction terms for year were modeled to examine group differences over time.Depending on the outcome, Turkish and Former Yugoslavian nationals had an 23%-69% higher chance of a poor treatment effectiveness than Germans (OR = 1.23 [95%-CI = 1.15,1.32] and OR = 1.69 [95%-CI = 1.55,1.83], respectively). Fewer differences were observed between nationals from Portugal/Spain/Italy/Greece and Germans. Disparities did not significantly differ between the years in which services were utilized.Measures implemented by health care institutions did not reduce existing health care disparities between immigrants and the majority population in Germany. One potential reason is that existing approaches are unsystematic and often not properly evaluated. More targeted strategies and a thorough evaluation is needed in order to improve health care for immigrants sustainably.